(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
In this paper, I will propose a re-attribution for a mould-blown Roman glass cup found in Villa Bartolomea, near Verona, and already published in the Corpus of Archaeological Glass Collections in Veneto as a cup of Syrian or Italian production. The decorative pattern of the cup can be compared to the one of a recently published glass cup found in the Augusteum of the Croatian city of Narona, which is marked by the famous glassmaker Aristeas the Cypriot, dated to the beginning of the 1st century AD. Together with Ennion, Aristeas is reputed one of the finest Roman glassmakers, and is one of the few known by its name.